Low-dose non-targeted radiation effects in human esophageal adenocarcinoma cell lines. (1st February 2017) - Hanu, Christine; Wong, Raimond; Sur, Ranjan K.; Hayward, Joseph E.; Seymour, Colin; Mothersill, Carmel
Abstract: Purpose: To investigate non-targeted radiation effects in esophageal adenocarcinoma cell lines (OE19 and OE33) using human keratinocyte and colorectal cancer cell reporters following γ-ray exposure. Materials and methods: Both clonogenic assays and ratiometric calcium endpoints were used to check for the occurrence of bystander signals in reporter cells. Results: We report data suggesting that γ-irradiation increases cell killing over the expected linear quadratic (LQ) model levels in the OE19 cell line exposed to doses below 1 Gy, i.e. which may be suggestive to be a low hyper-radiosensitive (HRS) response to direct irradiation. Both EAC cell lines (OE19 and OE33) have the ability to produce bystander signals when irradiated cell conditioned medium (ICCM) is placed onto human keratinocyte reporters, but do not seem to be capable of responding to bystander signals when placed on their autologous reporters. Further work with human keratinocyte reporter models showed statistically significant intracellular calcium fluxes following exposure of the reporters to ICCM harvested from both EAC cell lines exposed to 0.5 Gy. Conclusion: These experiments suggest that the OE19 and OE33 cell lines produce bystander signals in human keratinocyte reporter cells. However, the radiosensitivity of the EAC cell lines used in this study cannot be enhanced by the bystander response since both cell lines could not respond to bystander signals.